Nitrogen-doped TiO2 nanospheres for advanced sodium-ion battery and sodium-ion capacitor applications. Issue 47 (16th November 2016) - Liu, Sainan; Cai, Zhenyang; Zhou, Jiang; Pan, Anqiang; Liang, Shuquan
Abstract : We synthesized nitrogen-doped anatase TiO2 nanospheres, and then used them as high-performance anode materials for NIBs and NICs, which were found to display enhanced electrochemical performances. Abstract : Sodium-ion batteries (NIBs) and sodium-ion capacitors (NICs) are considered to be promising energy storage systems for applications in future hybrid electric vehicles (HEVs) and electric vehicles (EVs) because of the low cost and abundance of Na. Herein, NIBs and NICs based on nitrogen-doped TiO2 (referred to as N-TiO2 ) nanospheres as anode materials were analyzed. The N-TiO2 nanospheres exhibited a stable capacity of 162 mA h g −1 over 1000 cycles at 1 A g −1, as well as a superior rate performance in NIBs. In NICs, the N-TiO2 //AC device displayed a high energy density of ∼80.3 W h kg −1, a high power density of ∼12 500 W kg −1, and excellent long-term cycling stability for up to 6500 cycles.